Photonuclear reactions cross-sections at energies up to 100 MeV for different experimental setups - Deiev, O.S.; Timchenko, I.S.; Olejnik, S.M.; Potin, S.M.; Kushnir, V.A.; Mytrochenko, V.V.; Perezhogin, S.A.; Bocharov, V.А.; Shramenko, B.I. (Problems of Atomic Science and Technology, 2022)
In experiments on the electron linac LUE-40 of RDC “Accelerator” NSC KIPT, the flux-averaged cross-sections ⟨σ(Еγmax)⟩exp of photonuclear reactions ¹⁰⁰Mo(γ,n)⁹⁹Mo, ²⁷Al(γ,x)²⁴Na, ⁹³Nb(γ,n)⁹²ᵐNb, ⁹³Nb(γ,3n)⁹⁰Nb, and ¹⁸¹Ta(γ,n)¹⁸⁰ᵍTa were measured using the γ-activation technique. The theoretical flux-average cross-sections ⟨σ(Еγmax)⟩th were computed using the partial cross-section σ(Е) values from the TALYS1.9-1.95 codes and brems-strahlung γ-flux calculated using GEANT4.9.2. Two different experimental setups were used in the experiments: an aluminum electron absorber and a deflecting magnet to clean the bremsstrahlung γ-flux from electrons. A comparison of the flux-average cross-sections measured for two experimental setups was performed. The possibility of using the reactions ¹⁰⁰Mo(γ,n)⁹⁹Mo, ²⁷Al(γ,x)²⁴Na, ⁹³Nb(γ,n)⁹²ᵐNb, ⁹³Nb(γ,3n)⁹⁰Nb, and ¹⁸¹Ta(γ,n)¹⁸⁰ᵍTa as monitors of the bremsstrahlung γ-flux for the energy range 30…100 MeV was investigated. В експериментах на лінійному прискорювачі електронів ЛУЕ-40 НДК “Прискорювач” ННЦ ХФТІ були виміряні середні за гальмівним потоком перерізи ⟨σ(Еγmax)⟩exp для фотоядерних реакцій ¹⁰⁰Mo(γ,n)⁹⁹Mo, ²⁷Al(γ,x)²⁴Na, ⁹³Nb(γ,n)⁹²ᵐNb, ⁹³Nb(γ,3n)⁹⁰Nb, and ¹⁸¹Ta(γ,n)¹⁸⁰ᵍTa з використанням γ-активаційної методики. Теоретичні середні перерізи ⟨σ(Еγmax)⟩th були розраховані з використанням значень парціальних перерізів σ(Е) з кодів TALYS1.9-1.95 і гальмівний поток з GEANT4.9.2. У дослідженні використовувалися дві різні експериментальні установки: з алюмінієвим поглиначем електронів і відхиляючим магнітом для очищення потоку гальмівного випромінювання від електронів. Проведено порівняння середніх за гальмівним потоком перерізів, виміряних на двох експериментальних установках. Досліджено можливість використання реакцій ¹⁰⁰Mo(γ,n)⁹⁹Mo, ²⁷Al(γ,x)²⁴Na, ⁹³Nb(γ,n)⁹²ᵐNb, ⁹³Nb(γ,3n)⁹⁰Nb, та ¹⁸¹Ta(γ,n)¹⁸⁰ᵍTa у якості моніторів гальмівного γ-потоку при енергіях 30…100 МеВ.